A Novel Metal-Based Imaging Probe for Targeted Dual-Modality SPECT/MR Imaging of Angiogenesis - Tsoukalas, Charalampos; Psimadas, Dimitrios; Kastis, George A.; Koutoulidis, Vassilis; Harris, Adrian L.; Paravatou-Petsotas, Maria; Karageorgou, Maria; Furenlid, Lars R.; Moulopoulos, Lia A.; Stamopoulos, Dimosthenis; Bouziotis, Penelope (Frontiers in Chemistry, 2018)
Superparamagnetic iron oxide nanoparticles with well-integrated multimodality imaging properties have generated increasing research interest in the past decade, especially when it comes to the targeted imaging of tumors. Bevacizumab (BCZM) on the other hand is a well-known and widely applied monoclonal antibody recognizing VEGF-A, which is overexpressed in angiogenesis. The aim of this proof-of-concept study was to develop a dual-modality nanoplatform for in vivo targeted single photon emission tomography (SPET) and magnetic resonance imaging (MRI) of the tumor vascularization. Iron oxide nanoparticles (IONPs) have been coated with dimercaptosuccinic acid (DMSA), for consequent functionalization with the monoclonal antibody BCZM radiolabeled with 99mTc, via well-developed surface engineering. The IONPs were characterized based on their size distribution, hydrodynamic diameter and magnetic properties. In vitro cytotoxicity studies showed that our nanoconstruct does not cause toxic effects in normal and cancer cells. Fe3O4-DMSA-SMCC-BCZM-99mTc were successfully prepared at high radiochemical purity (>92%) and their stability in human serum and in PBS were demonstrated. In vitro cell binding studies showed the ability of the Fe3O4-DMSA-SMCC-BCZM-99mTc to bind to the VEGF-165 isoform overexpressed on M-165 tumor cells. The ex vivo biodistribution studies in M165 tumor-bearing SCID mice showed high uptake in liver, spleen, kidney and lungs. The Fe3O4-DMSA-SMCC-BCZM-99mTc demonstrated quick tumor accumulation starting at 8.9 ± 1.88 %ID/g at 2 h p.i., slightly increasing at 4 h p.i. (16.21 ± 2.56 %ID/g) and then decreasing at 24 h p.i. (6.01 ± 1.69 %ID/g). The tumor-to-blood ratio reached a maximum at 24 h p.i. (~ 7), which is also the case for the tumor-to-muscle ratio (~ 18). Initial pilot imaging studies on an experimental gamma-camera and a clinical MR camera prove our hypothesis and demonstrate the potential of Fe3O4-DMSA-SMCC-BCZM-99mTc for targeted dual-modality imaging. Our findings indicate that Fe3O4-DMSA-SMCC-BCZM-99mTc IONPs could serve as an important diagnostic tool for biomedical imaging as well as a promising candidate for future theranostic applications in cancer.